Highly conductive PEDOT:PSS films by post-treatment with dimethyl sulfoxide for ITO-free liquid crystal display - Chou, Tsu-Ruey; Chen, Szu-Hua; Chiang, Yen-Te; Lin, Yi-Ting; Chao, Chih-Yu (Journal of materials chemistry. C, Materials for optical and electronic devices, 2015)
In this study, a simple and effective method to enhance the conductivity of poly(3,4-ethylenedioxythiphene):poly(styrenesulfonate) (PEDOT:PSS) thin films from 0.7 to 1185 S cm −1 by post-treatment with dimethyl sulfoxide (DMSO) is demonstrated. After the rubbing technique was applied, the DMSO-treated PEDOT:PSS film could be used as both the transparent electrode and the alignment layer to fabricate ITO-free liquid crystal (LC) cells. The electro-optical properties of LC cells fabricated by the rubbed PEDOT:PSS were comparable to those constructed by ITO and polyimide. This work indicates that the highly conductive PEDOT:PSS film is a promising material for ITO-free LC devices. This work shows that the highly conductive PEDOT:PSS film is a promising material as both the transparent electrode and the alignment layer to replace ITO for ITO-free LC displays.